School-Based Resources as Protective Factors from the Influence of Parental Incarceration on Depressive Symptoms. (October 2020) - Finkeldey, Jessica G.; Dennison, Christopher R.
Although research on the deleterious effects of parental incarceration is extensive, few studies have examined factors that may attenuate these consequences. This study uses data from the National Longitudinal Study of Adolescent to Adult Health to examine the relationship between experiencing parental incarceration during childhood and depressive symptoms in young adulthood. Most importantly, it considers the degree to which this relationship is moderated by the availability of secondary-school-based resources. Results suggest that the consequences of parental incarceration on depressive symptoms are weaker for adolescents who attend schools that provide emotional counseling or nursing services on school premises or employ at least 50 percent of teachers with a master's degree or higher. These findings suggest that the availability of school resources contributes to adolescents' long-term resilience despite facing adverse circumstances.